2011
DOI: 10.1007/s13369-011-0167-0
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Study of the Mechanism of an Inverse-Demand Diels–Alder Reaction

Abstract: Quantum mechanical calculations (AM1, PM3, ab initio HF/3-21G, DFT(B3LYP/6-31G*) and MP2 //(B3LYP/6-31G*) have been used to study the inverse-demand synchronous concerted Diels-Alder reactions between dimethyl-1,2,4,5-tetrazine-3,6-dicarboxylate (diene) and a variety of dienophiles (ethylene, cyclopentadiene, 1-hexene, cyclohexene). All the molecular structures (reactants, transition states, intermediates and adducts) were optimized using the semi-empirical AM1 method. The calculated energies and volumes showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
1
2
0
Order By: Relevance
“…Shihab et al later studied a related reaction of a series of dienophiles with dimethyl 1,2,4,5-tetrazine-3,6-dicarboxylate by theoretical methods [52]. Their results are in agreement with the catalytic cycle presented in Scheme 1.…”
Section: Introductionsupporting
confidence: 52%
“…Shihab et al later studied a related reaction of a series of dienophiles with dimethyl 1,2,4,5-tetrazine-3,6-dicarboxylate by theoretical methods [52]. Their results are in agreement with the catalytic cycle presented in Scheme 1.…”
Section: Introductionsupporting
confidence: 52%
“…However, calculations that showed that the activation energy of the one-step pathway is almost 50 kcal mol −1 higher than that for the stepwise pathway later dismissed this view and predicted that a stepwise mechanism was preferred. 107 More recently, it was computationally determined that the barrier for the loss of nitrogen from the tetraazabarrelene intermediate is essentially nonexistent. Therefore, there are two sequential transition states, the first for the cycloaddition, and the second for the loss of N 2 to generate a pyridazine.…”
Section: 11mentioning
confidence: 94%
“…Therefore, they hypothesized that the cycloaddition and elimination of nitrogen occurred in a single asynchronous step, wherein the C–C bonds form and C–N bonds break simultaneously. However, calculations that showed that the activation energy of the one-step pathway is almost 50 kcal mol –1 higher than that for the stepwise pathway later dismissed this view and predicted that a stepwise mechanism was preferred . More recently, it was computationally determined that the barrier for the loss of nitrogen from the tetraazabarrelene intermediate is essentially nonexistent.…”
Section: Inverse-electron Demand Diels-alder Cycloaddition Reactionsmentioning
confidence: 99%